Swine Dendritic Cell Response to Porcine Reproductive and Respiratory Syndrome Virus: An Update - Hernández, Jesús; Li, Yanli; Mateu, Enric (Frontiers in Immunology, 2021)
Dendritic cells (DCs) are the most potent antigen-presenting cells, unique to initiate and coordinate the adaptive immune response. In pigs, conventional DCs (cDCs), plasmacytoid DCs (pDCs), and monocyte-derived DCs (moDCs) have been described in blood and tissues. Different pathogens, such as viruses, could infect these cells, and in some cases, compromise their response. The understanding of the interaction between DCs and viruses is critical to comprehend viral immunopathological responses. Porcine reproductive and respiratory syndrome virus (PRRSV) is the most important respiratory pathogen in the global pig population. Different reports support the notion that PRRSV modulates pig immune response in addition to their genetic and antigenic variability. The interaction of PRRSV with DCs is a mostly unexplored area with conflicting results and lots of uncertainties. Among the scarce certainties, cDCs and pDCs are refractory to PRRSV infection in contrast to moDCs. Additionally, response of DCs to PRRSV can be different depending on the type of DCs and maybe is related to the virulence of the viral isolate. The precise impact of this virus-DC interaction upon the development of the specific immune response is not fully elucidated. The present review briefly summarizes and discusses the previous studies on the interaction of in vitro derived bone marrow (bm)- and moDCs, and in vivo isolated cDCs, pDCs, and moDCs with PRRSV1 and 2.